A versatile UCST-type composite microsphere for image-guided chemoembolization and photothermal therapy against liver cancer. Issue 38 (30th September 2020) - Huang, Dan; Dai, Haitao; Tang, Keyu; Chen, Bin; Zhu, Hongzhang; Chen, Dubo; Li, Nan; Wang, Yingzhao; Liu, Chuwei; Huang, Yonghui; Yang, Jianyong; Zhang, Chao; et al.
Abstract : A versatile UCST-type composite microsphere for image-guided chemoembolization and photothermal therapy to enhance therapeutic response of liver cancer. Abstract : The development of novel chemoembolization agents to improve the treatment efficacy of transarterial chemoembolization (TACE) against liver cancer remains an urgent need in clinical practice. Herein, a versatile composite microsphere with upper critical solution temperature (UCST) properties was prepared to encapsulate polydopamine coated superparamagnetic iron oxide nanoparticles (SPION@PDA) and doxorubicin for simultaneous chemoembolization and photothermal therapy. The microspheres were spherical with an average diameter of 100–300 μm and exhibited favorable drug loading capability as well as strong photothermal effect. Strikingly, synergistic enhancement of photothermal therapy and chemotherapy against chemoresistant liver cancer cells was achieved. The in vivo therapeutic efficacy and safety evaluations were performed using rabbit VX2 liver tumor models. It was revealed that a single treatment of the combination of TACE and photothermal procedure resulted in 87.5% complete response and 12.5% partial response for the microsphere group, whereas all tumors in the control group progressed rapidly. Contrast-enhanced computed tomography (CT) evaluation indicated that the tumor diameter decreased by 91.5% after treatment, while that in the control group increased by 86.5%. The pathology-proven tumor necrotic rate was 87.2%, which significantly surpassed that of 65.2% in the control group. Furthermore, serum liver enzyme and biochemical studies indicated a temporary liver injury which can be fully recovered. Our findings demonstrated that this microsphere may be advantageous for enhancing therapeutic efficacy of TACE against liver cancer.